Analisis Manajemen Kredit Anggota Pada Koperasi Simpan Pinjam Ramai Lancar Ende - Marsel Nande; Valentina N. Raja (Program Studi Pendidikan Ekonomi FKIP Universitas Flores, 2025)
Saving and loan coorporate have a strategic role in empowering the community's economy, but face serious challenges in the form of bad credit which can threaten operational sustainability. This research aims to analyze the factors that cause bad credit in savings and loan cooperatives and identify appropriate prevention strategies. The research used a qualitative approach with a case study design at the busy Koperasi simpan pinjam in Ende. Data was collected through in-depth interviews with 5 informants consisting of cooperative administrators, borrower members and related departments. Data analysis uses thematic analysis techniques with an inductive approach. Research findings on the causes of bad credit are divided into three categories: (1) internal cooperative factors including weak credit analysis systems, lack of supervision, and unprofessional management; (2) external factors include macroeconomic conditions, business competition and natural disasters; (3) customer factors include the borrower's bad character, inability to pay, and misuse of credit. The conclusion is that bad credit in savings and loan cooperatives is caused by complex interactions between internal, external and customer factors. It is necessary to strengthen the risk management system, increase human resource capacity, and apply the principle of prudence in credit distribution.